Effects of the V/III ratio on the quality of aluminum nitride grown on (0001) sapphire by high temperature hydride vapor phase epitaxy. Issue 3 (24th January 2013) - Coudurier, N.; Boichot, R.; Fellmann, V.; Claudel, A.; Blanquet, E.; Crisci, A.; Coindeau, S.; Pique, D.; Pons, M.; Toropov, Alexey; Ivanov, Sergey
Abstract A High Temperature Hydride Vapor Phase Epitaxy reactor (HT‐HVPE) was used to grow 5 µm‐thick (0001) epitaxial AlN layers on sapphire. The experimental set‐up consists of a vertical cold‐wall quartz reactor working at low pressure in which the reactions take place on a graphite susceptor heated by induction. The reactants used are ammonia (NH3) and aluminum chlorides (AlClx) in situ formed via chlorine (Cl2) reaction with high purity aluminum pellets. As‐grown AlN layers have been characterized by Scanning Electron Microscopy (SEM), X‐ray diffraction rocking curves (XRC) and Raman spectroscopy. First, the influence of the V/III ratio in the gas phase on surface morphology, crystalline quality and strain into the material is investigated in order to improve the quality of epitaxial AlN layers grown at high temperature. Parameters were adjusted to keep constant growth rate of about 5 µm/h. Second, a protective layer (growth of a 200 nm‐thick AlN layer at 1200 °C) was deposited before the main growth of a 5µm layer of AlN at 1500°C. A 430 arcsec FWHM value for the 0002 reflection of the AlN layer has been obtained for such experimental conditions. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)